PEDAGOGICAL CONDITIONS OF INDIVIDUALIZATIONS PROFESSIONALLY ORIENTED TRAINING FOREIGN LANGUAGES OF NON-LANGUAGE STUDENTS SPECIALTIES IN HIGHER PEDAGOGICAL INSTITUTIONS - S.O. Melikova (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the pedagogocal condition of individualization o f the professional oriented training o f students of non-inguistic specialities at higher educational establishments. The possibility of every student's effective training has been given.